2024
DOI: 10.1098/rstb.2023.0068
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary immunology to explore original antiviral strategies

Jean-Luc Imler,
Hua Cai,
Carine Meignin
et al.

Abstract: Over the past 25 years, the field of evolutionary developmental biology (evo–devo) has used genomics and genetics to gain insight on the developmental mechanisms underlying the evolution of morphological diversity of animals. Evo–devo exploits the key insight that conserved toolkits of development (e.g. Hox genes) are used in animals to produce genetic novelties that provide adaptation to a new environment. Like development, immunity is forged by interactions with the environment, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Innate immune signalling therefore passes information through bottlenecks: a few broadly conserved MAMPs activate the cascades that are present, and these cascades converge on just one or a few TFs. This bottleneck regulatory approach is also part of the hourglass model of ‘evo-devo’ and ‘evo-immuno’ dynamics, discussed in [ 11 ]—in immunology, they may reflect a trade-off between producing a rapid defence or a specific one ( box 1 ).…”
Section: Information Bottlenecks Lead To Generalist Immune Activationmentioning
confidence: 99%
“…Innate immune signalling therefore passes information through bottlenecks: a few broadly conserved MAMPs activate the cascades that are present, and these cascades converge on just one or a few TFs. This bottleneck regulatory approach is also part of the hourglass model of ‘evo-devo’ and ‘evo-immuno’ dynamics, discussed in [ 11 ]—in immunology, they may reflect a trade-off between producing a rapid defence or a specific one ( box 1 ).…”
Section: Information Bottlenecks Lead To Generalist Immune Activationmentioning
confidence: 99%
“…Reflecting on host–virus interactions, Imler et al . [ 2 ] next synthesize recent work which has shown that even closely related species have distinct immune response profiles. Drawing a parallel from the hourglass model of evolutionary development (evo-devo), Imler et al .…”
Section: Summary Of Articlesmentioning
confidence: 99%
“…Drawing a parallel from the hourglass model of evolutionary development (evo-devo), Imler et al . [ 2 ] describe ‘evo-immuno' dynamics. These dynamics act across multiple levels, from receptors to core signalling elements, which themselves regulate diverse effectors.…”
Section: Summary Of Articlesmentioning
confidence: 99%
“…One caveat of this approach is that it overlooks biodiversity and the fact that during the never-ending arms race between hosts and viruses, diversification of the portfolio of antiviral defenses is expected to occur in the hosts ( Daugherty and Malik 2012 ; Goodin et al 2016 ; McDougal et al 2022 ). When it comes to biodiversity, insects with their 1.2 million known species are unmatched, offering the opportunity to extend the repertoire of antiviral genes ( Jactel et al 2021 ; Imler et al 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery that injection of CDNs into flies induces a potent transcriptional response associated with antiviral protection provides a powerful means to identify antiviral genes in Drosophila , without the caveat of the stress reactions triggered by cell lysis or tissue damage associated with viral infection. This paves the way for evolutionary immunology studies aimed at comparing the repertoire of antiviral genes in different species ( Imler et al 2024 ). Here, we exploit the CDN STING-agonist injection assay to explore the evolution of STING-dependent antiviral immunity in 10 different Drosophila species.…”
Section: Introductionmentioning
confidence: 99%